Role of visceral adiposity in functional recovery after myocardial infarction in females - Zhukova, Yu.; Zak , M. (Journal of Education, Health and Sport, 2025)
Title: Visceral Adiposity and Functional Recovery After Myocardial Infarction in Obese Female Patients: A Prospective Cohort Study Background: Visceral adiposity is increasingly recognized as a critical determinant of myocardial infarction (MI) outcomes. Unlike general obesity, visceral fat contributes to systemic inflammation, endothelial dysfunction, and poor cardiac recovery, particularly in women. Despite its clinical significance, visceral adiposity is often under-assessed in post-MI rehabilitation. Objective: To evaluate the effect of visceral adiposity on functional recovery and rehabilitation outcomes in obese female patients following a first myocardial infarction. Methods: A prospective study was conducted from 2020 to 2024 at the City Hospital No. 1 in Mykolaiv, Ukraine. Sixty female patients with class I obesity (BMI 30.0–34.9 kg/m²) and a first acute MI comprised the main group; 20 normoweight female MI patients (BMI 18.0–24.9 kg/m²) served as controls. All patients underwent standardized treatment, including revascularization and pharmacotherapy, followed by a multimodal rehabilitation program. The Visceral Adiposity Index (VAI), ejection fraction (LVEF), 6-minute walk distance, and NYHA functional class were assessed at discharge and after rehabilitation. Statistical analysis used ANOVA and correlation tests. Results: At baseline, VAI was significantly higher in the obese group (1.5±0.1 vs. 1.0±0.1, p<0.05). While both groups improved after rehabilitation, patients with higher visceral fat showed lower gains in functional capacity. The 6-minute walk distance increased by 43±3 m in the obese group versus 52±5 m in controls (p<0.05). At follow-up, NYHA class II was more common in controls (66% vs. 58%), and systolic function was slightly better preserved (LVEF: 52.6±0.7% vs. 51.1±0.3%). Visceral adiposity correlated with reduced exercise tolerance, persistent inflammation, and suboptimal quality-of-life indicators. Conclusions: Visceral obesity negatively impacts post-MI rehabilitation outcomes, particularly among women. Elevated VAI is associated with reduced functional recovery, underscoring the need for individualized rehabilitation strategies that consider adipose distribution, cardiometabolic status, and sex-specific recovery trajectories. Incorporating VAI into routine assessment may enhance risk stratification and guide more effective post-MI interventions.